Metronomic Treatment with Low-Dose Trofosfamide Leads to a Long-Term Remission in a Patient with Docetaxel-Refractory Advanced Metastatic Prostate Cancer - Jochen Greiner; Rainer Küfer; Sven N. Reske; Volker Martin; Hartmut Döhner; Mark Ringhoffer (Case Reports in Medicine)
The treatment of metastatic prostate cancer patients refractory to androgen withdrawal and docetaxel therapy is currently discouraging and new therapeutic approaches are vastly needed. Here, we report a long-term remission over one year in a 68-year-old patient with metastatic docetaxel-refractory prostate cancer employing low-dose trofosfamide. The patient suffered from distant failure with several bone lesions and lymph node metastases depicted by a (11) C-Choline positron emission tomography/computerized tomography (PET/CT). After initiation of trofosfamide 100 mg taken orally once a day we observed a steadily decreasing PSA value from initial 46.6 down to 2.1 𝜇g/l. The Choline-PET/CT was repeated after 10 months of continuous therapy and demonstrated a partial remission of the bone lesions and a regression of all involved lymph nodes but one. Taken together we found an astonishing and durable activity of the alkylating agent trofosfamide given in a metronomic fashion. We rate the side effects as low and state an excellent therapeutic ratio of this drug in our patient.